Rare earth elements in parasol mushroom Macrolepiota procera. (15th April 2017) - Falandysz, Jerzy; Sapkota, Atindra; Mędyk, Małgorzata; Feng, Xinbin
Highlights: Data on 16 REEs composition of parasol mushroom. Cerium was the most abundant among the REEs. Eating a tasty caps would not result in a health risk because of exposure to the REEs. Abstract: This study aimed to investigate occurrence and distribution of 16 rare earth elements (REEs) in edible saprobic mushroom Macrolepiota procera, and to estimate possible intake and risk to human consumer. Mushrooms samples were collected from sixteen geographically diverse sites in the northern regions of Poland. The results showed that for Ce as the most abundant among the RREs in edible caps, the mean concentration was at 0.18 ± 0.29 mg kg −1  dry biomass. The mean concentration for Σ16 REEs determined in caps of fungus was 0.50 mg kg −1  dry biomass and in whole fruiting bodies was 0.75 mg kg −1  dry biomass. From a point of view by consumer, the amounts of REEs contained in edible caps of M. procera could be considered small. Hence, eating a tasty caps of this fungus would not result in a health risk for consumer because of exposure to the REEs.